Soil biodiversity and network complexity jointly drive soil multifunctionality in an open cast coal mine - Xu, Caicai; Liu, Yong; Li, Junjian; Wang, Biao; Zhang, Hong (Frontiers in Microbiology, 2025)
IntroductionIntensive opencast coal mining has severely degraded soil ecosystem structure and function. Although ecological reclamation enhances soil biodiversity and multifunctionality (SMF), the underlying mechanisms—particularly how reclamation strategies influence SMF through the α-diversity, β-diversity, and network complexity of soil microbial and eukaryotic communities—remain unclear.MethodsWe employed a space-for-time substitution approach along a 30-year restoration chronosequence at the Antaibao opencast coal mine in northern China. The study included naturally restored grasslands and forests, artificially reclaimed vegetation, and unreclaimed bare land. We quantified SMF as the average Z-score of 19 soil variables related to nutrients, enzyme activities, and microbial biomass. Soil biodiversity (α- and β-diversity) and network complexity of bacterial, archaeal, fungal, and eukaryotic communities were assessed using high-throughput sequencing and topological network analysis.ResultsEcological reclamation significantly enhanced SMF, with mixed coniferous-broadleaf forests showing the highest level, followed by pure forests and grasslands. The α-diversity of all taxonomic groups and the β-diversity of bacteria and fungi were positively correlated with SMF. Artificially reclaimed sites increased network complexity in bacterial and archaeal communities but reduced it in eukaryotes. Random Forest and multiple regression analyses identified bacterial and fungal β-diversity as the dominant predictors of SMF recovery, followed by the network complexity of bacteria, archaea, and eukaryotes.DiscussionOur findings demonstrate that reclamation strategy influences SMF through shifts in multidimensional soil biodiversity and network architecture. The results underscore the importance of integrating multi-taxon and multi-dimensional attributes—such as community composition and co-occurrence networks—to fully elucidate how soil communities drive ecosystem multifunctionality during restoration.